(untitled) (Acta Scientiarum. Animal Sciences, 2012)
This study aimed to evaluate increasing levels (0, 4, 8 and 12%) of acid silage viscera of surubim catfish as an alternative protein source on growth performance and apparent digestibility coefficients (ADC) for Nile tilapia. Weight gain (WG), feed intake (FI), feed conversion ratio (FCR), and protein efficiency ratio (PER) were evaluated. The digestibility for dry matter (DM), crude protein (CP), ether extract (EE), gross energy (GE) and availability of phosphorus (P) were also assessed. The experimental design was completely randomized with four treatments and four repetitions. The results indicated no difference (p > 0.05) for growth performance parameters. The ADC of CP of treatment containing 8% of silage was lower (p < 0.05) when compared to the others. On the other hand, for the GE, the same level provided a higher ADC (p < 0.05). In conclusion, acid silage viscera of surubim catfish can be included in diets for Nile tilapia up to 12%, with no negative effects on growth performance and digestibility as well as to reduce feed cost.